2013
DOI: 10.2134/jeq2012.0456
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Nitrate Polluting Activities through Clustering of Isotope Mixing Model Outputs

Abstract: Apportionment of nitrate (NO) sources in surface water and classification of monitoring locations according to NO polluting activities may help implementation of water quality control measures. In this study, we (i) evaluated a Bayesian isotopic mixing model (stable isotope analysis in R [SIAR]) for NO source apportionment using 2 yr of δN-NO and δO-NO data from 29 locations within river basins in Flanders (Belgium) and five expert-defined NO polluting activities, (ii) used the NO source contributions as input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…B is widely used in fertilizer, manure, and household products and is difficult to remove by sewage treatment (Barth 2000 Xue et al (2013) identified the NO − 3 sources in five polluted areas of the Flanders watershed in Belgium. The results showed that relatively high 11 B values, which were consistent with those found in agricultural manure, were associated with groundwater beneath agricultural areas and in groundwater below areas of agriculture and horticulture.…”
Section: Combining Nitrogen and Oxygen Isotopes Of Nitrate With Boronmentioning
confidence: 99%
“…B is widely used in fertilizer, manure, and household products and is difficult to remove by sewage treatment (Barth 2000 Xue et al (2013) identified the NO − 3 sources in five polluted areas of the Flanders watershed in Belgium. The results showed that relatively high 11 B values, which were consistent with those found in agricultural manure, were associated with groundwater beneath agricultural areas and in groundwater below areas of agriculture and horticulture.…”
Section: Combining Nitrogen and Oxygen Isotopes Of Nitrate With Boronmentioning
confidence: 99%
“…Because B is not affected by transformation processes, the combined use of δ 11 B and the dual isotopes of nitrate have great benefits of the correct identification of nitrate source. Xue et al [66], by using δ 15 N, δ 18 O and δ 11 B, found that the major sources of the nitrate of surface water in the Flanders area of Belgium were manure and domestic sewage. Widory et al [72] used δ 11 B to evaluate the contribution of domestic sewage to nitrate.…”
Section: Source Identification Of Nitrate In Surface Water By Nitrogementioning
confidence: 99%
“…This procedure continues until all instances are classified. A more detailed description of a decision tree model can be found in Xue et al (2013). WEKA 3.4.10 software was used to explore decision trees.…”
Section: Decision Tree Modelmentioning
confidence: 99%
“…Spruill et al (2002) successfully classified five NO 3 − sources (fertilizer on crops, fertilizer on golf courses, irrigation spray from hog wastes, and leachate from poultry litter and septic systems) in groundwater based on a classification tree model using N isotopes, anions and cations. The basis of a classification/decision tree model is the creation of a hierarchical tree based on a dataset of known classes, which is then used to predict classes from another independent dataset with the same parameters but unknown classes (Xue et al, 2013). The sites investigated in this study are located in an intensive agricultural region, where 66.5% of irrigation water comes from groundwater (Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%